Pengaruh Lifestyle , Brand Image Dan Word Of Mouth Terhadap Keputusan Pembelian Pada Friday Killer Di Kota Pamekasan - Al Fajar, Moh Hafiz; Wahono, Budi; Basalamah, Muhammad Ridwan (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research aims to test and explain the influence of lifestyle, brand image and word of mouth on purchasing decisions for the Friday Killer in Pamekasan City. This type of research is explanatory research. The data analysis method usedis multiple linier regressions analysis.the sampling technique used the Maholtra Formula with a sample size of 65 respondents. To solve problem in research using SPSS assistance. The results of this research are that lifestyle, brand image and word of mouth variables have a significant effect on purchasing decisions simultaneously and partially.  Keywords: Lifestyle, Brand Image, Word Of Mouth and Purchase Decisions